Meningkatkan Hasil Belajar Pendidikan Kewarganegaraan Melalui Strategi Active Learning: Improving Citizenship Education Learning Outcomes Through Active Learning Strategies - Kurniawan, Machful Indra (Universitas Muhammadiyah Sidoarjo, 2017)
This study aimed to know the effectiveness of active learning in Civic Education course at UMSIDA. This study used Classroom Action Research design with 2 cycles and 4 main activities in each cycle, namely planning, acting, observing, and reflecting. The researcher took 36 (3 male and 33 female) second semester students of Primary School Education Department, particularly A2 class, academic year 2015/2016 as the subjects of the study. The results showed that the students’ score got improved 72% in cycle I (26 students) and 86% in cycle 2 (31 students). In short, the implementation of active learning was able to increase the students’ learning outcome in Civic Education course.